The synthesis and characterization of biotin-silver-dendrimer nanocomposites as novel bioselective labels - Malý, J; Lampová, H; Semerádtová, A; Stofik, M; Kovácik, L (Nanotechnology, 2009)
This paper presents a synthesis of a novel nanoparticle label with selective biorecognition properties based on a biotinylated silver-dendrimer nanocomposite (AgDNC). Two types of labels, a biotin-AgDNC (bio-AgDNC) and a biotinylated AgDNC with a poly(ethylene)glycol spacer (bio-PEG-AgDNC), were synthesized from a generation 7 (G7) hydroxyl-terminated ethylenediamine-core-type (2-carbon core) PAMAM dendrimer (DDM) by an N,N'-dicyclohexylcarbodiimide (DDC) biotin coupling and a NaBH(4) silver reduction method. Synthesized conjugates were characterized by several analytical methods, such as UV-vis, FTIR, AFM, TEM, ELISA, HABA assay and SPR. The results show that stable biotinylated nanocomposites can be formed either with internalized silver nanoparticles (AgNPs) in a DMM polymer backbone ('type I') or as externally protected ('type E'), depending on the molar ratio of the silver/DMM conjugate and type of conjugate. Furthermore, the selective biorecognition function of the biotin is not affected by the AgNPs' synthesis step, which allows a potential application of silver nanocomposite conjugates as biospecific labels in various bioanalytical assays, or potentially as fluorescence cell biomarkers. An exploitation of the presented label in the development of electrochemical immunosensors is anticipated.
Keywords: Models, Molecular; Enzyme-Linked Immunosorbent Assay; Surface Plasmon Resonance; nanokompozity; Microscopy, Electron, Transmission; povrchová plasmonová rezonance; Avidin; ELISA; barvení a značení; dendrimery; Nanocomposites; Polyamines; polyaminy; mikroskopie atomárních sil; Silver; Spectrophotometry, Ultraviolet; Kinetics; Staining and Labeling; transmisní elektronová mikroskopie; molekulární modely; kinetika; Dendrimers; avidin; Biotin; Spectroscopy, Fourier Transform Infrared; Microscopy, Atomic Force; spektrofotometrie ultrafialová; stříbro; biotin; spektroskopie infračervená s Fourierovou transformací